Local Labor Market Conditions and Crime: Evidence from the Brazilian Trade Liberalization - Rafael Dix-Carneiro; Rodrigo R. Soares; Gabriel Ulyssea (Institute for the Study of Labor (IZA), 2016)
This paper estimates the effect of local labor market conditions on crime in a developing country with high crime rates. Contrary to the previous literature, which has focused exclusively on developed countries with relatively low crime rates, we find that labor market conditions have a strong effect on homicides. We exploit the 1990s trade liberalization in Brazil as a natural experiment generating exogenous shocks to local labor demand. Regions facing more negative shocks experience large relative increases in crime rates in the medium term, but these effects virtually disappear in the long term. This pattern mirrors the labor market responses to the trade shocks. Using the trade liberalization episode to design an instrumental variables strategy, we find that a 10% reduction in expected labor market earnings (employment rate earnings) leads to a 39% increase in homicide rates. Our results highlight an additional dimension of adjustment costs following trade shocks that has so far been overlooked in the literature.
Keywords: F16; J23; J24; K42; 330; labor markets; crime; trade liberalization